IMPROVING STUDENTS’ WRITING ACHIEVEMENT THROUGH FLOWCHART MEDIA - Elfira Lutfi; Ari Nurweni; Lilis Sholihah (English Language Education Study Program, 2026)
This research measured the improvement in the students’ writing skills in writing explanation text using flowchart media. Pretest and posttest were used as instruments for data collection. The students were known to experience some difficulties, especially in organizing their ideas systematically regarding the topic to be written and some make mistakes in writing vocabulary according to the pretest results. While the posttest results showed an increase in students’ writing which becomes more organized. From the statistical analysis, the mean score of the students increased by 7.00 after the flowchart media was implemented. The t-value obtained was 8.885 with a degree of freedom (df) of 35, therefore the t-table obtained was 2.030. The level of significance showed a value of 0.000 or less than the probability of 0.05 and indicates a significant increase in the students’ writing skills. In other words, the use of flowchart media significantly helped to improve the students’ writing skills.